REMNANTS OF OTTOMAN LAW AND ITS APPLICATION IN CONTEMPORARY TIMES IN LEBANON AND THE ARAB WORLD - Kamaluddin, Safrudin Halimiy (UIN Imam Bonjol Padang, 2021)
At the beginning of the sixteenth century (1516), the Ottomans controlled all the lands that are today within the Lebanese Republic, and their existence lasted for four hundred years, during which they established military, security, administrative and social systems and enacted laws to improve and organize the country. Although five centuries have passed since the Ottoman presence in Lebanon, some of these laws are still in force. Some have been amended, such as the personal status law related to Islamic Law, some administrative regulations, and the municipal ordinance that the French updated during the Mandate days (1920-1943). While Ottoman laws are still strictly enforced in Lebanon, such as the Associations Law. Two sources, one legal and the other specialized in Islamic history, confirm in two separate interviews to Anadolu Agency the importance of these laws for Lebanon since their enactment until today.